2011
DOI: 10.1080/17470218.2010.495408
|View full text |Cite
|
Sign up to set email alerts
|

Ideomotor effects of pitch on continuation tapping

Abstract: The ideomotor principle predicts that perception will modulate action where overlap exists between perceptual and motor representations of action. This effect is demonstrated with auditory stimuli. Previous perceptual evidence suggests that pitch contour and pitch distance in tone sequences may elicit tonal motion effects consistent with listeners' implicit awareness of the lawful dynamics of locomotive bodies. To examine modulating effects of perception on action, participants in a continuation tapping task p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
4
17
2
Order By: Relevance
“…That is, larger changes in pitch did not elicit stronger effects on timing than smaller changes in pitch, suggesting that the degree of pitch change is not related to the magnitude of the observed timing effects. This result is contrary to results obtained by Ammirante et al (2010Ammirante et al ( , 2011, who reported that ITI and TV mirrored implied tonal acceleration in melodies (Ammirante, Thompson & Russo, 2011;Ammirante & Thompson, 2010). Results described in Experiment 1 and 2 did not reveal differences in tapping intervals and velocity related to the size or direction of the pitch change.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…That is, larger changes in pitch did not elicit stronger effects on timing than smaller changes in pitch, suggesting that the degree of pitch change is not related to the magnitude of the observed timing effects. This result is contrary to results obtained by Ammirante et al (2010Ammirante et al ( , 2011, who reported that ITI and TV mirrored implied tonal acceleration in melodies (Ammirante, Thompson & Russo, 2011;Ammirante & Thompson, 2010). Results described in Experiment 1 and 2 did not reveal differences in tapping intervals and velocity related to the size or direction of the pitch change.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have shown that melodic contour change with great pitch distances elicited faster ITI and tap velocity, whereas pitch contour that implied negative accelerations induced slower tapping intervals, suggesting that there may be a fine tune between auditory feedback and timing (Ammirante, Thompson & Russo, 2011;Ammirante & Thompson, 2010). Perceptual studies also demonstrated similar illusions as findings suggested that a melody containing fewer contour changes is judged as faster than target, even when sequences were isochronous (Boltz, 1998).…”
Section: Experiments 2: Unexpected Small Pitch Changessupporting
confidence: 63%
See 3 more Smart Citations